Semi‐Siccative Oils and Bioactive Fractions Isolated from Reunion Island Fruit Co‐Product: Two Case Studies. Issue 4 (25th February 2019) - Delvar, Alice; de Caro, Pascale; Caro, Yanis; Shum Cheong Sing, Alain; Thomas, Rudy; Raynaud, Christine
Abstract : This paper focused on the use of agro‐industrial wastes of strawberry guava ( Psidium cattleianum ) and passion fruit ( Passiflora edulis ) generated by the agricultural industry on Reunion Island, according to two routes: extraction of semi‐siccative oils from the seeds and extraction of bioactive compounds from residual pulp and peels. Oil content, fatty acid, carotenoids, tocopherol, and sterol concentrations are determined in the seed oils obtained by four different extraction processes using Soxhlet extraction, extraction by hexane and ethanol, mechanical pressing and supercritical‐carbon dioxide (SC‐CO2 ) extraction. The oil extraction yields ranged from 15 to 30% w/w for strawberry guava and passion fruit, respectively. Both oils are classified as semi‐siccative and had a similar total unsaturated fatty acid content (88%) with a prevalence of linoleic acid (70–78%). High contents in phytosterols and in α‐tocopherol are particularly detected in strawberry guava oil. The antioxidant activities of the bioactive compounds extracted by water and ethanol from pulp and peels are characterized by α, α‐diphenyl‐β‐picrylhydrazyl (DPPH) test. After purification on polymeric resin, significant antioxidant activities are recorded (half maximal inhibitory concentration (IC50 ) from 11 to 50 g L −1 ) and are related to polyphenol contents (20.7 to 42.5 g gallic acid equivalents (GAE)/100 g dry extract). Practical Applications : There is a great interest on the use of tropical fruit wastes because of their large availabilities. Strawberry guava and passion fruit are often used in the food industry, for juice and jam production. The seeds, pulp, and peel residues are in fact a by‐product of their industrial processing, which should be valuably processed instead of just throwing away. We can state that the extracted seed (rich in polyunsaturated fatty acids) of strawberry guava and passion fruit can be used in the industrial production of emulsions, paints, and varnishes. Within the positive aspects of the study, one can also distinguish the use of these tropical fruit by‐products as beneficial sources of many valuable bioactive compounds, for example, carotenoids, tocopherols, phytosterols, and especially polyphenols, for functional formulations. Moreover, it may be the experimental basis for further development and use in food industry Green extraction processes are applied to two tropical fruit coproducts. Seed oils obtained are rich in unsaturated fatty acids (88%). Strawberry guava oil has high contents in α‐tocopherol and in sterols. Functional organic molecules are also isolated from residual peels and pulps. Results shows that strawberry guava extracts have antioxidant activities similar to Trolox. Abstract : Green extraction processes are applied to two tropical fruit coproducts. Seed oils obtained are rich in unsaturated fatty acids (88%). Strawberry guava oil has high contents in α‐tocopherol and in sterols. Functional organic molecules are also isolated from residual peels and pulps. Results shows that strawberry guava extracts have antioxidant activities similar to Trolox.